Studies on age related changes in serum biochemical and enzymic profile in male Surti goats - JADAV, P V; SARVAIYA, N P; PATEL, D M (The Indian Journal of Animal Reproduction, 2023)
The age related changes in biochemical profile of serum, viz. total protein, cholesterol, alkaline phosphatase and inorganic phosphorous were studied at fortnightly interval in 21 growing male Surti goats and were correlated with their growth rate. The experimental animals were divided equally into three groups with 6-9, 9-12 and 12-18 months of age. The study revealed that the total cholesterol and total protein levels increased with advancement of age, whereas the serum alkaline phosphatase (AKP) activity was found to be decreased. The mean levels of total protein were 7.30 ± 0.06, 7.47 ± 0.09 and 8.03 ± 0.07 g/dl, total cholesterol 64.47 ± 1.53, 67.61 ± 2.24 and 70.50 ± 1.60 mg/di, AKP 266.16 ± 7.89, 232.51 ± 8.51 and 144.31 ± 8.76 IU/I, and inorganic phosphorus 13.41± 0.38, 12.08 ± 0.42 and 13.01 ± 0.47 mg/di, in age group I, II and III respectively. The effect of age and period was significant for all the traits, but their iriteraction was not significant. The serum inorganic phosphorous levels tended to remain static up to one year of.age and then it declined. The serum cholesterol and total protein levels had similar trend as found with testosterone levels in different groups of Surti bucks, but similar trend was not observed either for serum AKP or inorganic phosphorous levels.